Conception of complex estimation methodology of ecological compatibility for territorial and object systems - Касимов, Олександр Меджитович; Козуля, Тетяна Володимирівна; Ємельянова, Дар’я Ігорівна; Козуля, Марія Михайлівна; Гагарін, Віталій Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Theoretical practical bases of justification of ecological compatibility estimation method is given in the article and is based upon probabilistic entropic risk analysis for solving ecological security problems at the level of landscape geochemical complexes and territorial object systems.